Evaluating average throughput for quantity of data stream in an NDN rendezvous server - Ahmed, Muhammed Zaharadeen; Hassan Abdalla Hashim, Aisha; Mohd. Ramli, Huda Adibah; Majikumna, Kaloma Usman (Science and Engineering Research Support Society, 2020)
This paper evaluates throughput to improve interest and data content transmission in the proposed distributed rendezvous server stream. An anchor within the network core is not considered but hence anchorless connection is adopted to aid routing between different locations of producer and rendezvous servers.This technique is simulated to present a seamless communication between producers and rendezvous servers.Using ndnSIM 2.1, performance analysis is measured to determine best route forwarding strategy and ensure minimal signalling cost and overhead. The mobile producers and servers were interfaced with Wireshark to capture packet and analyse the network statistics for throughput (moving average), segment length, round-trip time, sequence number and window scaling.